FEATURES OF CIVIC EDUCATION OF STUDENTS IN THE “SCHOOL–MAHALLA” SYSTEM IN UZBEKISTAN - Khaydarov Shavkat Shamsiddin Ogli (Western European Studies, 2025)
The article examines modern theoretical concepts of civic education and their adaptation to the context of Uzbekistan. Particular attention is paid to the “School–Mahalla” model as an integrative form of interaction between educational institutions, the family, and the local community. The key factors in the formation of civic identity are analyzed, including traditional values, digital transformation, and intercultural dialogue. It is shown that this model combines national educational traditions with universal democratic values and contributes to the development of socially responsible and civically mature individuals.
Keywords: civic education; identity; school; mahalla